Synthesis of poly(butyl acrylate)‐poly(methyl methacrylate) core–shell nanomaterials of anti‐crease‐whitening properties. Issue 7 (24th October 2013) - Zhang, Wenjing; Mu, Luye; Wang, Yun; Lin, Shaohui; Pan, Qinmin
ABSTRACT Core–shell nanomaterials of poly(butyl acrylate)‐poly(methyl methacrylate) were synthesized using a differential microemulsion polymerization method for being used as polyacrylate‐based optical materials, which meet the requirement of anti‐crease‐whitening and proper mechanical strength. The effects of reaction temperature and surfactant amount on the particle sizes, as well as the effect of reaction temperature on the conversion and solid content were investigated to reveal the dependence of the application properties on the reaction conditions. The spherical morphology of core–shell nanoparticles was also studied via transmission electron microscopy. The resulting polymers with a core–shell monomer ratio of butyl acrylate/methyl methacrylate at 32/10 (vol/vol) demonstrated the optimal balanced properties in the anti‐crease‐whitening and mechanical property, confirmed by the visible light transmittance measurement and the dynamic analysis of the viscoelastic properties of the synthesized core–shell nanomaterials. The smaller the particle size, the better the transparency of the resulting polymer films. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39991.